EVALUATION OF SOME INDICATORS AFTER SIMULATED CLINICAL MORTALITY IN FEMALE RATS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
From the first day of the post-resuscitation period to the 21st day in rats that experienced clinical death, against the background of the dominance of the sympathetic nervous system of an increase in the amounts of FSH and LH, estradiol in the blood. On the 21st day of the post-intensive care period, the predominance of the activity of the prooxidant system of indicators of endogenous intoxication and a decrease in the coefficient of protein stability in reducing hormone synthesis in the reproductive system was established